A Parametric Study of a Fully Passive Oscillating Foil Turbine on a Swinging Arm in a Tandem Configuration - Dominic Cloutier; Mathieu Olivier; Guy Dumas (Energies)
A fully passive oscillating foil turbine on a swinging arm in a tandem configuration consisting of two NACA 0015 foils at both ends of its arm and operating in an incompressible flow at a Reynolds number of <semantics>3.9×106</semantics> is investigated with numerical simulations. The turbine is free to oscillate passively in response to hydrodynamic forces and structural reactions from springs and dampers. The passive motion of the tandem turbine arises from a transfer of energy from the flow, and this motion is solved using a fluid-structure algorithm coupling the Newtonian dynamics of the system with two-dimensional, unsteady, and Reynolds-averaged Navier–Stokes equations. The performance metrics, i.e., the efficiency and power coefficient, of the proposed turbine concept are explored with a momentum gradient ascent algorithm, which uses the near-optimal configuration of an equivalent single-foil concept from a previous study as a starting point. These starting configurations consist of tandem foils operating either under coupled flutter or stall flutter instabilities. The use of gears to adjust the equilibrium position of the pitching motion is also considered, resulting in a total of four baseline configurations. The best configuration found with the gradient ascent algorithm presents an efficiency value near <semantics>75%</semantics> and a power coefficient of <semantics>1.46</semantics>, showing the great potential of fully passive oscillating foil turbines operating in a tandem configuration and providing valuable insight for further development of this technology through three-dimensional simulations and prototype testing.